BABA-Induced DNA Methylome Adjustment to Intergenerational Defense Priming in Potato to Phytophthora infestans - Kuźnicki, Daniel; Meller, Barbara; Arasimowicz-Jelonek, Magdalena; Braszewska-Zalewska, Agnieszka; Drozda, Andżelika; Floryszak-Wieczorek, Jolanta (Frontiers in Plant Science, 2019)
We provide evidence that alterations in DNA methylation patterns contribute to the regulation of stress-responsive gene expression for an intergenerational resistance of β-aminobutyric acid (BABA)-primed potato to Phytophthora infestans. Plants exposed to BABA rapidly modified their methylation capacity towards genome-wide DNA hypermethylation. De novo induced DNA methylation (5-mC) correlated with the up-regulation of Chromomethylase 3 (CMT3), Domains rearranged methyltransferase 2 (DRM2), and Repressor of silencing 1 (ROS1) genes in potato. BABA transiently activated DNA hypermethylation in the promoter region of the R3a resistance gene triggering its downregulation in the absence of the oomycete pathogen. However, in the successive stages of priming, an excessive DNA methylation state changed into demethylation with the active involvement of potato DNA glycosylases. Interestingly, the 5-mC–mediated changes were transmitted into the next generation in the form of intergenerational stress memory. Descendants of the primed potato, which derived from tubers or seeds carrying the less methylated R3a promoter, showed a higher transcription of R3a that associated with an augmented intergenerational resistance to virulent P. infestans when compared to the inoculated progeny of unprimed plants. Furthermore, our study revealed that enhanced transcription of some SA-dependent genes (NPR1, StWRKY1, and PR1) was not directly linked with DNA methylation changes in the promoter region of these genes, but was a consequence of methylation-dependent alterations in the transcriptional network.